The Relationship Between Students' Attitudes Towards Geography Lessons and Learning Motivation and Geography Learning Achievement - Elvia, Rosi; Emiola, Adetoun Gladys; Quynh, Pham Thi Ngoc (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to determine the relationship between students' attitudes towards geography lessons and the relationship between learning motivation and students' geography learning achievement. Methodology:This research is a descriptive study whose population is all high schools in Surakarta. The sample for this research was 79 students of class XI IPS. Data collection is carried out through questionnaires, tests, observations and documents. The data was then analyzed using multiple linear regression with three analysis prerequisites: normality test, multicollinearity test, and heterogeneity test. Main Findings: The findings of this research are as follows. First, there is no positive correlation between students' attitudes towards Geography and their learning outcomes. This is indicated by a probability value of 0.231; which is higher than 0.05. Second, there is a positive relationship between student motivation and learning outcomes, with a probability value of 0.018. The third finding is that there is a simultaneous relationship between students' attitudes and motivation and their learning outcomes, with a probability value of 0.033. Novelty/Originality of this study: The novelty of this research is that it provides information about the relationship between students' attitudes towards geography lessons and learning motivation with students' geography learning outcomes so that it can be used as material for consideration in learning strategies by Geography subject teachers.